Innovations for inclusive and sustainable growth of domestic food value chains: Fruits and vegetables value chains in Nigeria scoping report - Takeshima, Hiroyuki; Yamauchi, Futoshi; Balana, Bedru; Adeyanju, Dolapo; Edeh, Hyacinth O.; Kadjo, Didier; Liverpool-Tasie, Saweda Lenis Onipede; Abdoulaye, Tahirou; Yegbemey, Rosaine Nerice; Ayenan, Mathieu; Olanipekun, Caleb Ibukun (International Food Policy Research Institute, 2023)
Fruits & vegetable value chains (F&V VC) in Nigeria hold significant potential to continue toward sustainable, inclusive food system transformation. Domestic food system growth, including that of F&V, remains crucial in achieving a healthy food environment and serving as a source of various micronutrients. There is a need for bundles of innovations to address multiple challenges along F&V VC in Nigeria, characterized by a set of challenges that are unique to developing countries and F&V.